Research on Wind Flow Control by Windbreak Fence for a Large Radio Telescope Site Based on Numerical Simulations - Feilong He; Qian Xu; Na Wang (Advances in Astronomy)
The higher the pointing accuracy of the radio telescope, the more obvious the influence of wind disturbance on antenna performance. Taking the site of the 110 m aperture QiTai radio Telescope (QTT) as an example, the terrain and air flow characteristics of the site are studied. It is found that the wind direction with high incoming wind frequency and relatively high speed is mostly located in the mountain gap on the periphery of the antenna. If the wind resistance facilities are precisely arranged in the upstream tuyere, the wind speed in the antenna area can be effectively reduced. This study proposes a method to control the wind flow at a telescope site based on the precise arrangement of the windbreak fence. The windbreak fence simulation model is constructed using the theory of porous jump. The mean error of the simulation results is less than 14% compared to the wind tunnel measured data, indicating that the constructed windbreak fence model has high reliability. The computational domain model of the working conditions for the site is constructed. The extreme condition of the windbreak fence arrangement is considered, and the simulation results show that the wind speed in the antenna area can be reduced by more than 30% through the control of the windbreak fence. It verifies the feasibility of the method of controlling the wind flow by the windbreak fence for the site which provides a reference for the subsequent research on the precise arrangement of the windbreak fence.